2018
DOI: 10.1007/s11606-018-4417-7
|View full text |Cite
|
Sign up to set email alerts
|

Interventions That Support or Involve Caregivers or Families of Patients with Traumatic Injury: a Systematic Review

Abstract: Studies showed mixed patterns of intervention effects on caregiver and patient outcomes; evidence about intervention impact is inconclusive. This review is the first to identify caregiving interventions for patients with TBI and polytrauma and extends past reviews about patients with PTSD. Limitations include a small evidence base, low study quality, disparate methods, varied outcome measures, and high heterogeneity. PROSPERO Registration CRD42017053516.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…It is known that a high frequency of singular and plural first pronoun usage is an indicator of depression and PTSD 25,[73][74][75][76][77][78] . We examined singular first pronoun occurrence in text data from Holocaust survivors, controls and PTSD sufferers, consisting of people who experienced trauma years ago, including childhood trauma.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that a high frequency of singular and plural first pronoun usage is an indicator of depression and PTSD 25,[73][74][75][76][77][78] . We examined singular first pronoun occurrence in text data from Holocaust survivors, controls and PTSD sufferers, consisting of people who experienced trauma years ago, including childhood trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Strengthening caregiver skills, support, and connection to health system resources, can reduce burden [6,7] and psychological symptoms [8] and improve the ability of caregivers to care for patients at home [9][10][11]. However, systematic reviews of interventions for caregivers of multiple patient populations show mixed results [12][13][14][15][16]. By and large these systematic reviews were rigorously designed and included randomized controlled trial (RCT) design studies which lend credence to these results.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews (Kreitzer, Kurowski, & Bakas, 2018;Shepherd-Banigan et al, 2018) have identified several other studies with a similar focus on dyad-based interventions for people with TBI. These interventions have targeted areas such as providing education, problem-solving support, advocacy training and strategies relating to cognition, behaviour, interpersonal skills and home environment (Brown et al, 2015;Moriarty et al, 2016;Powell, Fraser, Brockway, Temkin, & Bell, 2016;Sinnakaruppan, Downey, & Morrison, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We designed this protocol using a rigorous approach to minimise risk of bias. Systematic reviews within the field of TBI interventions have noted methodological shortcomings of previous research (Kreitzer et al, 2018;Shepherd-Banigan et al, 2018). Recommendations to improve the quality and rigour of intervention studies include randomisation of participants, description of participants' severity of cognitive impairments, reporting of treatment fidelity, larger sample sizes, follow-up of participants over time, consideration of intervention acceptability and quality of life measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation